2018
DOI: 10.1371/journal.pone.0205115
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization period before capturing an ultra-short vagal index can be shortened to 60 s in endurance athletes and to 90 s in university students

Abstract: PurposeTo find the shortest, acceptable stabilization period before recording resting, supine ultra-short-term Ln RMSSD and heart rate (HR).MethodThirty endurance-trained male athletes (age 24.1 ± 2.3 years, maximal oxygen consumption (VO2max) 64.1 ± 6.6 ml·kg-1·min-1) and 30 male students (age 23.3 ± 1.8 years, VO2max 52.8 ± 5.1 ml·kg-1·min-1) were recruited. Upon awaking at home, resting, supine RR intervals were measured continuously for 10 min using a Polar V800 HR monitor. Ultra-short-term Ln RMSSD and HR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…These studies reported excellent validity and sensitivity of 1 min ultra-short-term HRV record during a 5 min stabilization period. For nonathletic population, Krejčí et al [42] demonstrated that 90 s of LnRMSSD mean record can provide strong agreement of HRV measurements in collegiate students. It is interesting to note that these studies conducted the HRV measures in pre and post-training periods or a cross-sectional time point.…”
Section: Discussionmentioning
confidence: 99%
“…These studies reported excellent validity and sensitivity of 1 min ultra-short-term HRV record during a 5 min stabilization period. For nonathletic population, Krejčí et al [42] demonstrated that 90 s of LnRMSSD mean record can provide strong agreement of HRV measurements in collegiate students. It is interesting to note that these studies conducted the HRV measures in pre and post-training periods or a cross-sectional time point.…”
Section: Discussionmentioning
confidence: 99%
“…Heart rate variability Heart rate variability (HRV) was measured in a supine position using a Garmin Forerunner 920XT monitor. Before starting three-minute data collection [29], a one-minute stabilization period was performed [30]. Subjects were able to breathe at their natural rhythm.…”
Section: Recovery Measurementsmentioning
confidence: 99%
“…HRV has primarily been studied in individual sports [14][15][16][17][18] owing to its usefulness in monitoring adaptation to training in athletes [1,4,10,11,13,[15][16][17][18][19][20][21][22]. Of particular interest is a recent study that focused on stabilization time that indicated that it must differ depending on the level of the athlete [23]. They suggested different stabilization times for different sports and athletic levels.…”
Section: Introductionmentioning
confidence: 99%
“…In summary, two main issues are considered important with regard to ultra-short HRV measurements in male professional soccer players, including 1) the validity of the 1-minute registration time for this special population, and 2) the previous stabilization time. In this respect, more studies are required because stabilization times may differ depending on the population being studied [23]. Therefore, the two main aims of this study were as follows: 1) to compare 1-minute RMSSD measurements using different stabilization times as well as the conventional 5-minute stabilization time and measurement; and 2) to determine the agreement between every 1-minute RMSSD measurement with the conventional 5-minute criterion, both in professional soccer players.…”
Section: Introductionmentioning
confidence: 99%